2005
DOI: 10.1089/ars.2005.7.1664
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Nrf2 Activation by Oxidative Stress

Abstract: The capacity of cells to maintain homeostasis during oxidative stress resides in activation or induction of protective enzymes. Nuclear-factor-E2-related factor (Nrf)-2 as a member of bZIP transcription factors is expressed in a variety of tissues. Transcriptional activation of antioxidant genes through an antioxidant response element (ARE) is largely dependent upon Nrf2. The genes that contain a functional ARE include those encoding GSTA1, GSTA2, NAD(P)H:quinone reductase, and gamma-glutamylcysteine synthetas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
231
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(239 citation statements)
references
References 60 publications
5
231
0
3
Order By: Relevance
“…It is more likely that hemoglobin exerts pleiotropic effects in these cells; it modulates the cellular responses to various oxidants and free radicals (NO, superoxide, H 2 O 2 , peroxynitrite, and so on); hemoglobin, either through acting on membrane receptors or via modulation of intracellular pathways and signal transduction processes, may also regulate the expression of various oxidant-responsive elements (as evidenced, in our study, by the hemoglobin-induced upregulation of HIF-1α and NRF2). Upregulation of both of these factors is known to confer cytoprotection and ischemic/hypoxic preconditioning via a variety of interacting downstream pathways (28,29). Intracellular hemoglobin shows remarkable compartmentalization; it concentrates to the mitochondria, where it shows a particularly close association with mitochondrial complex I.…”
Section: Discussionmentioning
confidence: 99%
“…It is more likely that hemoglobin exerts pleiotropic effects in these cells; it modulates the cellular responses to various oxidants and free radicals (NO, superoxide, H 2 O 2 , peroxynitrite, and so on); hemoglobin, either through acting on membrane receptors or via modulation of intracellular pathways and signal transduction processes, may also regulate the expression of various oxidant-responsive elements (as evidenced, in our study, by the hemoglobin-induced upregulation of HIF-1α and NRF2). Upregulation of both of these factors is known to confer cytoprotection and ischemic/hypoxic preconditioning via a variety of interacting downstream pathways (28,29). Intracellular hemoglobin shows remarkable compartmentalization; it concentrates to the mitochondria, where it shows a particularly close association with mitochondrial complex I.…”
Section: Discussionmentioning
confidence: 99%
“…10,68,69 Transcription of the HO-1 gene is under the control of antioxidant response element, which is activated by the transcription factor, nuclear factor erythroid-2-related factor 2 (Nrf2). Activation of Nrf2 is typically induced by oxidative stress 70,71 and nitrosative stress (nitric oxide). 72 In this regard, the low expression of HO-1 in human microglia may in part be due to their inability to express iNOS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, heavy metals such as lead, cadmium and mercury may cause an increase in production of reactive oxygen species (ROS) (Ercal et al, 2001) and expression of ABCC2 has been demonstrated to be associated with elevated cellular ROS (Payen et al, 2001). The Nrf2 (nuclear factor-erythroid 2 p45-related factor 2) transcription factor, which binds the ARE sequences (antioxidant-response element; also named electrophile response element, EPRE) and regulates a battery of detoxifying and antioxidant genes in response to oxidative stress (Adachi et al, 2007;Kang et al, 2005) may be involved in the induction of abcc2 gene by these metals, since previous studies have demonstrated the existence of ARE elements in the promoters of human and mouse Abcc2 gene (Tanaka et al, 1999;Vollrath et al, 2006) and the involvement of ARE-Nrf2 pathway in the induction of Abcc2 gene by several xenobiotics (Vollrath et al, 2006). Therefore, it is of great interest to further study mechanisms underlying the tissuespecific expressing and the induction of zebrafish abcc2 gene by mercury and lead.…”
Section: Discussionmentioning
confidence: 99%